Failure analysis on welded joints of 347H austenitic boiler tubes. (November 2015) - Lee, Han-sang; Jung, Jine-sung; Kim, Doo-soo; Yoo, Keun-bong
Abstract: Microstructural and thermo-mechanical analyses using the finite element method (FEM) were performed on the welded joint of 347H boiler tubes in a coal-fired power plant after 3600 h of operation. The cracks in the failed tube started on the inner surface of the heat-affected zone (HAZ). This area had a high hardness value and volume fraction of strain-induced martensite. The plastic deformation around the crack was concentrated near the grain boundaries. This failure occurred as the stabilizing effect disappeared due to carbide dissolution in the heat-affected zone, and plastic deformation and tensile residual stress were formed at the inner side due to the solidification contraction of the outer bead. Highlights: The dissolution of Nb carbide and the hardness increase at the HAZ of as-welded specimen were found. The volume fraction of strain-induced martensite at HAZ of failed tube was high. The plastic deformation in HAZ by EBSD analysis concentrated around the grain boundary. Tensile residual stress and plastic deformation were highest at the inner surface of HAZ where the crack started.